APLIKASI PUPUK KANDANG KOTORAN SAPI PADA PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT (Capsicum frustescens L.) DI LAHAN RAWA LEBAK - Nur Hafizah; Rabiatul Mukarramah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2017)
Cayenne pepper beneficial for humans because it contains protein, fat, carbohydrates, vitamin A, vitamin B, vitamin C and minerals. Cow dung manure is a fertilizer that is derived from the cattle shed, either in the form of solid feces and urine mixed food scraps, manure cow manure composed of a mix of 0.5% N, 0.25% P, 0.5% K. The purpose of the study these are (1) study the response of the growth and yield of cayenne pepper on the application of cow dung manure in swampy wetlands, (2) determine the dose best cow dung manure on growth and yield of rawit chil cayenne pepper i in swampy wetlands. This research was conducted in the village of Teluk Sarikat Banjang District of Hulu Sungai Utara from May to August 2014, using a randomized block design with 6 treatments and 4 groups. The treatment consisted of (p0) 0 ton.ha-1 (p1) 10 ton.ha-1 (p2) 20 ton.ha-1 (p3) 40 ton.ha-1, (p4) 40 ton.ha-1, (p5) 50 ton.ha-1. The results showed that the application of cow dung manure real impact on the number of branches, number of pieces, weight of the fruit crop in the ground cayenne pepper in swampy wetlands. Dose best cow dung manure in this study was 20 ton.ha-1 is equivalent to 80 g.polybag-1 (p2).